In silico screening and experimental validation identify riboflavin as an RNA-targeted antiviral against SARS-CoV-2 - Chae-Hong Jeong; Yoo Jin Na; Tae Yong Kim; So Young Lee; Jungyeon Kim; Sangmi Ryou (Scientific Reports)
Abstract This study explored drug repurposing strategies against conserved RNA structures in the SARS-CoV-2 genome to address viral mutation challenges. Conserved RNA elements were computationally identified by aligning 283 SARS-CoV-2 genomes from Korean patients. RNA secondary structures were predicted using RNAfold and RNAstructure, followed by virtual screening of 11 compounds using the RNALigands database (binding energy threshold: -6.0 kcal/mol). The antiviral activity and cytotoxicity of riboflavin were experimentally validated in vitro using Vero E6 cells infected with SARS-CoV-2 (MOI 0.01). Riboflavin exhibited selective antiviral activity against SARS-CoV-2 (IC50 = 59.41 µM), showing no cytotoxicity at concentrations < 100 µM. Riboflavin treatment during viral inoculation significantly reduced viral replication, whereas riboflavin treatment pre- or post-inoculation had no effect. The other screened compounds lacked antiviral efficacy. In terms of antiviral activity, riboflavin was less potent than remdesivir (IC50 = 25.81 µM). Riboflavin is a potential RNA-targeted therapeutic agent against SARS-CoV-2. This study established a framework for integrating computational and experimental methods to identify conserved RNA targets, thus offering a strategy applicable to other RNA viruses. This result indicates the potential of riboflavin as a broad-spectrum antiviral agent against SARS-CoV-2 and highlights the importance of considering nutritional factors in the context of viral infections.